2019
DOI: 10.1111/head.13635
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal‐Targeted Treatments in Migraine: Is 60% the Magic Number?

Abstract: Trigeminal‐targeted treatments (TTTs), the most specific and selective therapeutic migraine approach to date, are effective in approximately 60% of patients regardless of treatment type or mechanism, at least if used alone. Sixty percent is also the proportion of migraineurs who develop migraine‐like episodes following experimental intravenous administration of trigeminal neuropeptides and roughly 60% is the percentage of patients with a unilateral migraine tracing the area of cutaneous distribution of the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Translating the erenumab scientific evidence on erenumab into clinical practice through real-life studies does not only confirm its effectiveness, tolerability, and safety in a multifaceted clinical setting of patients with diverse comorbidities and multiple prior therapeutic failures, but also addresses different questions in migraine management such as response predictability and unraveling possible specific migraine endophenotypes. 17,[23][24][25] A placebo-controlled trial reported that erenumab responders are hypersensitive to CGRP infusion. 26 The positive association between basal CM frequency and erenumab responsiveness is in line with the finding of frequencydependent increase in interictal peripheral blood CGRP levels in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translating the erenumab scientific evidence on erenumab into clinical practice through real-life studies does not only confirm its effectiveness, tolerability, and safety in a multifaceted clinical setting of patients with diverse comorbidities and multiple prior therapeutic failures, but also addresses different questions in migraine management such as response predictability and unraveling possible specific migraine endophenotypes. 17,[23][24][25] A placebo-controlled trial reported that erenumab responders are hypersensitive to CGRP infusion. 26 The positive association between basal CM frequency and erenumab responsiveness is in line with the finding of frequencydependent increase in interictal peripheral blood CGRP levels in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanism underlying unilateral migraine pain is, in fact, a pronounced peripheral trigeminal sensitization, which is a process probably associated with an increased CGRP release and leading to a pain tracing the anatomical distribution of a hyperactive ophthalmic branch of the trigeminal nerve. Furthermore, migraine patients with unilateral pain, especially when associated with accompanying homolateral parasympathetic symptoms, are not only supposed to be super-responders to trigeminal-targeted treatments, but have also an increased central trigeminal sensitization 23,25,28,29. It is worth noting that the proportion of erenumab responders, we found (approximately 60%) is in line with that of other trigeminal-targeted treatments and of migraine patients who developed migraine-like episodes following the experimental intravenous administration of trigeminal neuropeptides 27.…”
mentioning
confidence: 99%
“…Inversely, the bilateral pain location in almost half of the patients (46.6%)-a proportion significantly higher than the average documented in large population series (~30%) 16 -is noteworthy and suggests a less crucial involvement of the trigeminovascular system, a central sensitization, or both, in these patients. 17,18 Insightful reflections arose from the description of CM development, progression, and management. CM started in a slow progressive fashion ~20 years after EM onset, usually without any CM appears to be caused by a unique mixture of bio-psychosocial aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is a clinically heterogeneous brain disorder despite its major subdivisions according to headache frequency and presence of aura (18). The search for migraine endophenotypes is still in its infancy but it may be useful not only to unravel pathophysiological mechanisms, but mostly to empower tailored therapy in the modern era of precision medicine (1821).…”
Section: Discussionmentioning
confidence: 99%